2022
DOI: 10.1101/2022.12.01.518708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partition complex structure can arise from sliding and bridging of ParB dimers

Abstract: Chromosome segregation is vital for cell replication and in many bacteria is controlled by the ParABS system. A key part of this machinery is the association of ParB proteins to the parS-containing centromeric region to form the partition complex. Despite much work, the formation and structure of this nucleoprotein complex has remained unclear. However, it was recently discovered that CTP binding allows ParB dimers to entrap and slide along the DNA, as well as leading to more efficient condensation through Par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…5D). Similar observations were made in previous modelling studies that indicated that the introduction of DNA supercoiling promoted the formation of partition complexes 35,36 . A recent study by Sekkouri Alaoui et al 58 however suggested no significant influence of supercoiling on the formation of partition complex in plasmids.…”
Section: The Impact Of Dna Supercoiling On Parbsupporting
confidence: 89%
See 3 more Smart Citations
“…5D). Similar observations were made in previous modelling studies that indicated that the introduction of DNA supercoiling promoted the formation of partition complexes 35,36 . A recent study by Sekkouri Alaoui et al 58 however suggested no significant influence of supercoiling on the formation of partition complex in plasmids.…”
Section: The Impact Of Dna Supercoiling On Parbsupporting
confidence: 89%
“…In previous in vivo and in vitro studies, ParB proteins were shown to be proficient at forming DNA condensates around the parS site 15,16,18,45,56,57 , and various current models suggest a strong dependence on ParB diffusion and self-self interaction. Notably, distant-site binding due to supercoiling-related proximity could severely alter the formation of ParB-DNA condensates, such as was proposed recently by Connolley et al 35 .…”
Section: Supercoiling Facilitates Dna Condensation By Parb Proteinsmentioning
confidence: 86%
See 2 more Smart Citations
“…Thus, for all other parameters being equal, the DoD-mode remained in fully extended conformation while MoD-mode dynamically collapsed the DNA into a condensed state. Notably, a recent model on the ParB:DNA condensation in Caulobacter crescentus suggests that DoD-mode could bring DNA into a condensed cluster ( 54 ). In this model, this is facilitated by the rapid re-formation of the ParB-ParB bridge after the proteinprotein connection is broken, whereby both proteins remain bound to the DNA.…”
Section: Cooperativity Of Parb Multimers Drives Parb:dna Condensationmentioning
confidence: 99%